Impact of fetal and neonatal malnutrition on the onset of puberty and associated noncommunicable disease risks - Nicholas E Connor (Dove Medical Press, 2011)
Nicholas E ConnorChild Health Research Foundation Dhaka Shishu Hospital, Dhaka, BangladeshBackground: Fetal and neonatal malnutrition impacts the timing of the onset of puberty. The timing of puberty onset has been shown to be a rough indicator of noncommunicable disease (NCD) risk. Recent advances in understanding the various inter-related neurochemical and genetic controls underpinning puberty onset have shed new light on these interesting and important phenomena. These studies have suggested that developmental trajectory is set very early by epigenetic mechanisms that serve to adjust phenotype to environment.Objective: The aims of this article are to review the most recent research into the proximate mechanisms that initiate puberty; to explore how the activation of those mechanisms could be affected by nutritional cues received during fetal and neonatal life; and, finally, to briefly explore the ramifications for public health.Methods: An extensive literature review was performed using PubMed (1950 to September 2010) and Google Scholar (1980 to September 2010) using the search terms “puberty onset”, “perinatal”, and “neonatal malnutrition”. English language, original research, and review articles were examined; pertinent citations from these articles were also assessed.Results: Literature detailing biochemical pathways and evolutionary explanations of human puberty itself led quickly to a noteworthy connection between neonatal malnutrition, puberty onset, and NCD risk. A strong connection was found between maternal malnutrition during critical windows (followed by catch-up growth in childhood) and an accelerated onset of puberty. Children subject to early nutritional insult not only are likely to undergo puberty earlier but also show an increase in their risk of developing NCDs in later life. Several authors have suggested that this relationship may show potential as an early proxy indicator of susceptibility to these types of diseases, which are an increasing concern in both affluent and developing countries.Conclusions: More attention should be paid to fetal and neonatal nutrition and puberty onset if we are to meaningfully curb the troubling growth of NCDs now and in the future. Efforts to improve maternal conditions among vulnerable poor groups as well as more affluent groups worldwide should be explored, especially among groups undergoing rapid nutritional transition.Keywords: malnutrition, early puberty onset, IUGR, maternal health, maternal capital, NCD risk, kisspeptin, leptin, fetal programming